PERSEKUTUAN KOMANDITER SEBAGAI SUBJEK PEMEGANG HAK GUNA BANGUNAN BERDASARKAN SURAT EDARAN MENTERI ATR/BPN NOMOR 2/SE-HT.02.01/VI/2019 - Biya, Cokorda Istri Brahmi Putri; Rudy, Dewa Gde (Acta Comitas : Jurnal Hukum Kenotariatan, 2020)
This research is based on Circular Letter 2/SE- HT.02.01/VI/2019,   dated   June   28,   2019   concerning   the Granting of Building Use Rights for the Military Alliance (commanditaire vennootschap). This circular is a guideline for implementing the granting of HGB to the temporary Limited partnership companies (CV) when referring to Article 35 paragraph (1) of the Agrarian Law that Building Rights can only be owned by Indonesian Citizens and Legal Entities established under Indonesian law and domiciled in Indonesia, as also described in Article 19 Implementing Regulations, namely Government Regulation Number 40 of 1996 concerning Land Use Rights, Building Use Rights and Land Use Rights. Circular Number 2/SE-HT.02.01/VI/2019, dated June 28, 2019 concerning the granting of Building Rights for the Limited partnership companies(CV), cause a conflicts of legal norms between  laws  and  regulations  of  one  degree  or  another  or between laws and regulations in a hierarchical manner. Furthermore is the arising of legal uncertainty from the description above, the problems that can be raised in this study are: What is the legal position of the Limited partnership companies (CV) according to the legal provisions in Indonesia and whether the Limited partnership companies (CV) can be used as the subject of the Right to Use. This research uses the Normative legal research method by using a type of approach in the form of a statutory approach and an analytical conceptual approach. Sources of legal materials used in this study include primary, secondary and tertiary legal sources. The results of this study indicate that the legal status of limited partnership (CV) in Indonesian law is that Limited partnership companies(CV) is not a legal entity but only as a business entity. This can be assessed based on the characteristics of the legal entity that is the separation of assets of the state-owned companies with the assets of business entities, so that the state-owned companies are only responsible for the limited assets owned. Meanwhile, in CV, all active   (complementary)   and   passive   (limited   partnership)       companies may be held liable for losses suffered by CV, as Article 2 1  of the  Code of  Business Lawthat said  CV  companies has jointly responsible and jointly responsible (CV) cannot be the